2016
DOI: 10.1071/ah14168
|View full text |Cite
|
Sign up to set email alerts
|

Point prevalence of suboptimal footwear features among ambulant older hospital patients: implications for fall prevention

Abstract: Objective The aim of the present study was to establish the point prevalence of 'suboptimal' features in footwear reported to have been used by older hospital patients when ambulating, and to explore underpinning factors for their choice of footwear. Method A cross-sectional investigation was undertaken on 95 of 149 eligible in-patients across 22 high fall-risk wards in a large metropolitan hospital in Brisbane, Australia. Results Over 70% of participants experienced an unplanned admission. Although most parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Enclosed shoes generally provide better slip resistance than slippers, socks, or going barefoot, and they may be protective against future falls. We acknowledge, however, that this recommendation may be difficult to implement, as many older people base their footwear purchases on comfort [9] and wear slippers indoors [9][10][11][12]. As a pragmatic solution, it may be possible for older people who are not prepared to wear shoes indoors to instead wear slippers designed to maintain balance, as backless slippers impair balance [49] and provide a greater risk of fall-related injury [15] than enclosed slippers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enclosed shoes generally provide better slip resistance than slippers, socks, or going barefoot, and they may be protective against future falls. We acknowledge, however, that this recommendation may be difficult to implement, as many older people base their footwear purchases on comfort [9] and wear slippers indoors [9][10][11][12]. As a pragmatic solution, it may be possible for older people who are not prepared to wear shoes indoors to instead wear slippers designed to maintain balance, as backless slippers impair balance [49] and provide a greater risk of fall-related injury [15] than enclosed slippers.…”
Section: Discussionmentioning
confidence: 99%
“…One potentially modifiable risk factor that may contribute to falls in longterm care is footwear. The most frequently worn indoor footwear are slippers, which often comprise design features considered detrimental to balance, including lack of fixation, thick and soft midsoles, and smooth outersoles [9][10][11][12]. It has been shown that wearing slippers is a risk factor for falls [13][14][15] and fall-related injury [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The physician-led sixcomponent screening assessment included patient-reported foot and ankle pain or discomfort, footwear safety assessment, inspection for corns, calluses, and ulcers, paper grip testing, and neuropathy screening. These components were identified by the Royal Melbourne Hospital Podiatry team, following a MEDLINE literature review on foot-related risk factors associated with falls [30][31][32][33][34][35][36][37][38][39][40][41]. At the time of undertaking this study, there was literature available to suggest podiatry interventions were effective in addressing foot and ankle problems and consequently reduce falls risk.…”
Section: Patient Characteristicsmentioning
confidence: 99%